Study of Cellulose and Starch-Based Biodegradable Foam Production Technology as Enviromentally Packaging Materials - Rasdiana, Felga Zulfia; Refdi, Cesar Welya (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
Biodegradable foam is an alternative to styrofoam packaging which is not environmental friendly and harmful to health. Various sources of starch are widely available in nature which can be used as raw material for making biodegradable foam. Several researchers found that many types of starch can be used as the main material for making biodegradable foam, including cassava starch, corn starch, sago starch, durian seed starch, jackfruit seed starch, avocado seed starch, and banana weevil starch. The production methods used from several studies that have been carried out are thermopressing, baking process, microwave assisted molding, and extrusion. Biodegradable foam based on starch is brittle, sensitive to water and requires additional treatment to increase strength, flexibility and resistance to water so that it can be used commercially. The purpose of this article is to provide information on the production of biodegradable foam from various types of starch and cellulose. Based on the results of the analysis, the characteristics of biodegradable foam using the baking process method and modified sago starch resulted in better water absorption values compared to other types of starch and production methods.